2017
DOI: 10.3389/fphys.2017.00410
|View full text |Cite
|
Sign up to set email alerts
|

Bed Rest and Hypoxic Exposure Affect Sleep Architecture and Breathing Stability

Abstract: Objective: Despite over 50 years of research on the physiological effects of sustained bed rest, data characterizing its effects on sleep macrostructure and breathing stability in humans are scarce. This study was conducted to determine the effects of continuous exposure to hypoxia and sustained best rest, both individually and combined, on nocturnal sleep and breathing stability.Methods: Eleven participants completed three randomized, counter-balanced, 21-days trials of: (1) normoxic bed rest (NBR, PIO2 = 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…Acquisition of clinical, exercise, dietary, and ambiental data were described in detail before ( Debevec et al, 2014a , 2016a ; Simpson et al, 2016 ). The in-house database ( Sket et al, 2017b ) containing over 13,000 entries based on all measured variables in the PlanHab experiment (i.e., clinical, inflammation, immune, human physiology, and nutrition data next to the experimental design and characteristics of the participants) was checked for consistency and updated with recent publications related to the PlanHab project ( Debevec et al, 2014a , 2016b , 2018 ; Keramidas et al, 2016 ; Louwies et al, 2016 ; Rittweger et al, 2016 ; Rullman et al, 2016 , 2018 ; Simpson et al, 2016 ; Morrison et al, 2017 ; Strewe et al, 2017 ; Salvadego et al, 2018 ; Sarabon et al, 2018 ; Stavrou et al, 2018a , b ; Ciuha et al, 2020 ). The in-house database was used to identify parameters that differed significantly between the experimental variants over the course of the experiment as described before ( Sket et al, 2017b , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Acquisition of clinical, exercise, dietary, and ambiental data were described in detail before ( Debevec et al, 2014a , 2016a ; Simpson et al, 2016 ). The in-house database ( Sket et al, 2017b ) containing over 13,000 entries based on all measured variables in the PlanHab experiment (i.e., clinical, inflammation, immune, human physiology, and nutrition data next to the experimental design and characteristics of the participants) was checked for consistency and updated with recent publications related to the PlanHab project ( Debevec et al, 2014a , 2016b , 2018 ; Keramidas et al, 2016 ; Louwies et al, 2016 ; Rittweger et al, 2016 ; Rullman et al, 2016 , 2018 ; Simpson et al, 2016 ; Morrison et al, 2017 ; Strewe et al, 2017 ; Salvadego et al, 2018 ; Sarabon et al, 2018 ; Stavrou et al, 2018a , b ; Ciuha et al, 2020 ). The in-house database was used to identify parameters that differed significantly between the experimental variants over the course of the experiment as described before ( Sket et al, 2017b , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present work represents a sub-study of a large, international project funded by the European Union (Planetary Habitat Simulation – PlanHab) conducted at the Olympic Center in Planica, Slovenia that aimed to investigate physiological responses to simulated microgravity and normobaric hypoxia. Comprehensive methodological details of the PlanHab project ( Debevec et al, 2014a ) have already been published along with several physiological outcomes ( Debevec et al, 2016 ; Keramidas et al, 2016a , b ; Rittweger et al, 2016 ; Rullman et al, 2016 ; Simpson et al, 2016 ; Morrison et al, 2017 ; Sket et al, 2017a , b ; Strewe et al, 2017 , 2018 ; Šket et al, 2018 ; Stavrou et al, 2018a , b ). A brief summary of the projects’ key methodological features is provided below, but we kindly refer the readers to the above-mentioned papers for specific details.…”
Section: Methodsmentioning
confidence: 99%
“…Gut environment was explored from the perspective of ecosystem development [ 15 ] in order to elucidate the relationship between the progressive increase in stool consistency (MP, dry matter) and the progressive intestinal and systemic inflammation observed over the course of the PlanHab project. The MP values reported in this study were coupled to reanalysis of the PlanHab data and fecal 1H-NMR metabolomes reported before [ 3 , 13 , 14 ] to explore the association between stool consistency (MP), individual signatures in 1H-NMR metabolites and the elevated intestinal, systemic inflammation and other detrimental physiological deconditioning effects observed in the PlanHab participants reported before [ 3 , 13 , 14 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%